The Fenix reborn: Occupational therapy in the first humanitarian mission in Portugal. Issue 2 (3rd July 2021) - Roldão, Elisabete; Marques, Alexandra; Cavaleiro, Joana; Mendes, Diana; Sofia Oliveira, Ana
ABSTRACT: In Portugal, June 2017, there was a large fire, which was considered a national disaster. It led to changes in people's daily routines, affecting their occupational performance and making them vulnerable. At the time, the non-governmental organisation, Doctors of the World, implemented the first humanitarian mission in Portugal – The Hope Mission. This mission, which was made up of a nurse, a community mediator, two occupational therapists, four occupational therapy students and a clinical educator, intervened with the population of the entire affected region. Their main objective was to meet the needs of the people; involving them in significant activities, re-organising their roles and routines, re-structuring their daily lives, increasing their quality of life and their wellbeing and avoiding social isolation. Home visits, group activities and projects were implemented in partnership with community institutions. One of the projects was the (Re)Start Project. An initial assessment was made by the occupational therapists in order to plan the intervention. The project consisted of home visits (where an evaluation of the home context was made), group sessions (cognitive stimulation, motion sessions and group dynamics) and individual sessions (focusing on the performance issue and difficulties experienced by each person undertaking their daily routines). To understand the degree of satisfaction of the participants, specifically in relation to the (Re)Start project, a questionnaire was given to all who participated for more than one month. From analysis of the questionnaires, the conclusion was drawn that participants were satisfied with the activities developed in the project and found them meaningful. The presence of occupational therapy in this scenario was found to be important and made a difference. It would be useful to repeat this type of intervention at a national level, if a further humanitarian crisis occurs, especially in areas with ageing population or which are geographically isolated.